What have we learnt from histology about the efficacy of coronary imaging modalities in assessing plaque composition? - Yap, Nathan Angelo Lecaros; Khan, Zahid; He, Xingwei; Lee, Jae-Geun; Maung, Soe; Morgan, Kimberley R.; Zhou, Tingquan; Precht, Helle; Serruys, Patrick W.; Garcia-Garcia, Hector M.; Onuma, Yoshinobu; Hynes, Sean; et al. (Frontiers in Cardiovascular Medicine, 2025)
Accurate evaluation of coronary artery pathology is essential for risk stratification and tailoring appropriate treatment. Intravascular imaging was introduced for this purpose 40 years ago enabling for the first time in vivo plaque characterization. Since then, several studies have evaluated the efficacy of the existing intravascular imaging modalities in assessing plaque pathology and composition and their potential in guiding intervention and predicting vulnerable plaques. Today it is known that intravascular imaging is an indispensable tool in percutaneous coronary intervention planning, but the existing modalities have a limited efficacy in predicting lesion vulnerability; a fact that should be attributed to their advantages and limitations in accurately assessing morpho-pathological features that are common in advanced atherosclerotic plaques. This review aims to provide a comprehensive evaluation of the performance of intravascular imaging in characterizing plaque phenotypes using histology as a reference standard; it summarizes the studies comparing the available invasive imaging techniques against histology, discusses the findings and limitations of these studies and highlights the potential of novel intravascular imaging approaches that were introduced for a more complete and comprehensive evaluation of plaque pathobiology.